Juridical Review Regarding Cases of Corruption in Social Assistance Funds during the Covid-19 Pandemic - Kelly Chandra Puspita Halim; Marshanda Btari Sukmara; Mochammad Ridho Nasrullah; Shefira Amalia Choirunnisa (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The Covid-19 pandemic that has hit the world has had a major impact on the country's economy. Indonesia is one of many countries that are trying to restore economic conditions by holding government programs such as social assistance. However, the program was misused by Juliari P. Batubara as an official of the Minister of Social Affairs who committed the criminal act of corruption in aid funds for personal use. Therefore, these actions are very detrimental and must be held criminally accountable for the perpetrators in order to provide a deterrent effect. The results of this study are that the death penalty is appropriate for those who are not responsible for using social assistance funds belonging to underprivileged people. In the writing that we make, this writing is motivated by Pancasila and the Law. So have the authorities carried out the appropriate punishment for the perpetrators? This act has been regulated in Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. This research uses a normative method which is carried out by examining library materials or secondary data.